Vitamin A status regulates glucocorticoid availability in Wistar rats: consequences on cognitive functions and hippocampal neurogenesis? - Bonhomme, Damien; Minni, Amandine M.; Alfos, Serge; Roux, Pascale; Richard, Emmanuel; Higueret, Paul; Moisan, Marie-Pierre; Pallet, Véronique; Touyarot, Katia (Frontiers in Behavioral Neuroscience, 2014)
A disruption of the vitamin A signaling pathway has been involved in age-related memory decline and hippocampal plasticity alterations. Using vitamin A deficiency (VAD), a nutritional model leading to a hyposignaling of the retinoid pathway, we have recently demonstrated that retinoic acid (RA), the active metabolite of vitamin A, is efficient to reverse VAD-induced spatial memory deficits and adult hippocampal neurogenesis alterations. Besides, excess of glucocorticoids (GCs) occurring with aging is known to strongly inhibit hippocampal plasticity and functions and few studies report on the counteracting effects of RA signaling pathway on GCs action. Here, we have addressed whether the modulation of brain GCs availability could be one of the biological mechanisms involved in the effects of vitamin A status on hippocampal plasticity and functions. Thus, we have studied the effects of a vitamin A-free diet for 14 weeks and a 4-week vitamin A supplementation on plasma and hippocampal corticosterone (CORT) levels in Wistar rats. We have also investigated corticosteroid binding globulin (CBG) binding capacity and 11beta-Hydrosteroid Dehydrogenase type 1 (11β-HSD1) activity, both important modulators of CORT availability at the peripheral and hippocampal levels respectively. Interestingly, we show that the vitamin A status regulates levels of free plasma CORT and hippocampal CORT levels, by acting through a regulation of CBG binding capacity and 11β-HSD1 activity. Moreover, our results suggest that increased CORT levels in VAD rats could have some deleterious consequences on spatial memory, anxiety-like behavior and adult hippocampal neurogenesis whereas these effects could be corrected by a vitamin A supplementation. Thus, the modulation of GCs availability by vitamin A status is an important biological mechanism that should be taken into account in order to prevent age-related cognitive decline and hippocampal plasticity alterations.